Slowly Delivered Icariin/Allogeneic Bone Marrow-Derived Mesenchymal Stem Cells to Promote the Healing of Calvarial Critical-Size Bone Defects - Tianlin Liu; Xin Zhang; Yuan Luo; Yuanliang Huang; Gang Wu (Stem Cells International)
Bone tissue engineering technique is a promising strategy to repair large-volume bone defects. In this study, we developed a 3-dimensional construct by combining icariin (a small-molecule Chinese medicine), allogeneic bone marrow-derived mesenchymal stem cells (BMSCs), and a siliceous mesostructured cellular foams-poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (SMC-PHBHHx) composite scaffold. We hypothesized that the slowly released icariin could significantly promote the efficacy of SMC-PHBHHx/allogeneic BMSCs for repairing critical-size bone defects in rats. In in vitro cellular experiments, icariin at optimal concentration (10−6 mol/L) could significantly upregulate the osteogenesis- and angiogenesis-related genes and proteins, such as Runx2, ALP, osteocalcin, vascular endothelial growth factors, and fibroblast growth factors, as well as the mineralization of BMSCs. Icariin that was adsorbed onto the SMC-PHBHHx scaffold showed a slow release profile within a 2-week monitoring span. Eight weeks after implantation in calvarial critical-size bone defects, the constructs with icariin were associated with significantly higher bone volume density, trabecular thickness, trabecular number, and significantly lower trabecular separation than the constructs without icariin. Histomorphometric analysis showed that icariin was also associated with a significantly higher density of newly formed blood vessels. These data suggested a promising application potential of the icariin/SMC-PHBHHx/allogeneic BMSCs constructs for repairing large-volume bone defects in clinic.